Post medieval pottery in Lincolnshire 1450-1805 - White, Andrew (1989)
This thesis investigates the manufacture and use of ceramics over four centuries in Lincolnshire, and considers the evidence for date and function of the pottery itself and for the social standing and economy of the potters, late survivors of the medieval peasant craftsman tradition. Documentary and physical evidence are both searched to produce the most comprehensive possible list of sites and potters names, and to highlight the areas of doubt where neither type of source can give sufficient proof. The methods of pottery production are also examined and two specific types of vessels are discussed in detail as examples of the search for -=origins. From this point the search widens to consider the importation principally by sea of pottery from other parts of the country and from Europe, and the prices of such wares are compared with prices of local products. This leads to certain conclusions about the economic pressures on local potters and their adjustments to deal with new problems and changing expectations. Contemporary sources, depositional evidence and context are next used to study the names and function of pottery, and finally the principles of dating are discussed, and a series of pottery groups are analysed to test the reliability and transferability of dating. Throughout pottery making is compared with comparable trades and Lincolnshire's position with that of the wider ceramic world.